Divergent Multistep Continuous Synthetic Transformations of Allylic Alcohol Enabled by Catalysts Immobilized in Ionic Liquid Phases. Issue 8 (28th March 2019) - Peris, Edgar; Porcar, Raúl; García‐Álvarez, Joaquín; Burguete, María Isabel; García‐Verdugo, Eduardo; Luis, Santiago V.
Abstract: Two individual catalytic platforms (metal‐ and organo‐catalyzed) based on the use of an ionic liquid phase were successfully integrated for the synthesis of α‐cyano‐amine and cyanohydrin trimethylsilyl ethers from allylic alcohol. The right combination of continuous flow processes enabled access to the divergent preparation of two alternative and interesting intermediate compounds from the same starting material. Abstract : Choose your own adventure ! Distinct and individual catalytic platforms (metal‐ and organo‐catalyzed) based on the use of ionic liquids have been successfully integrated for the synthesis of α‐cyano‐amine and cyanohydrin trimethylsilyl ethers from allylic alcohol. Two alternative intermediate compounds can be obtained by selecting the appropriate conditions.